The design and microfabrication of a sub 100 mg insect‐scale flapping‐wing robot. (1st May 2017) - Zou, Yang; Zhang, Weiping; Ke, Xijun; Lou, Xingliang; Zhou, Sui
Abstract : A piezo‐actuated self‐lifting insect inspired flapping‐wing robot is presented. A novel method is presented in the work, which has taken into account the difficulties and the precision of assembly among micro components. Each component is properly designed and reasonably arranged to reduce the assembly difficulties of such insect‐scale robot. Specifically, the design of the piezoelectric actuator has taken into account the electrical isolation and assembly issues. The transmission and the airframe are integrated into one component to avoid assembly difficulties. Fibre directions of wing veins are reasonably arranged to possess high strength and stiffness. As a result, this robot, which weighs 84 mg with a wingspan of 35 mm, can generate sufficient thrust to take off with a flapping amplitude approximately ±60° under the resonant wingbeat frequency of 100 Hz.